Dark matter a guide to Alexander Kluge and Oskar Negt - Langston, Richard 1970- (Verso, 2020)
"Collaborators for more than four decades, lawyer, author, filmmaker, and multimedia artist Alexander Kluge and social philosopher Oskar Negt are an exceptional duo in the history of Critical Theory. Dark Matter argues that what makes their contributions to the Frankfurt School so remarkable is how they think together in spite of their enormous differences. At the core of all their work is a profound sense that the catastrophic conditions of modern life are not humandkind's unalterable fate. For Kluge and Negt, the huge mass of dark matter throughout the universe is analogous to those happier alternatives available to our calamitous world."
Keywords: Negt, Oskar -- 1934-2024; Kluge, Alexander -- 1932-